A fault diagnosis method based on stiffness evaluation model for full ceramic ball bearings containing subsurface cracks. (June 2023) - Li, Tao; Shi, Huaitao; Bai, Xiaotian; Zhang, Ke
Abstract: Most of the surface macroscopic faults of ceramic bearings are caused by the extended evolution of early subsurface cracks in mesoscopic and microscopic levels. Because of the greater contact stiffness and brittle failure mechanism of ceramic materials, the dynamic response becomes more sensitive, especially in the early failure stage with subsurface cracks. To evaluate the non-negligible effect for the cumulative expansion of subsurface cracks on the contact stiffness, this paper proposes a stiffness evaluation method based on the combination of theory and experiment. Combined with fracture mechanics, the quantified weakening effect of subsurface cracks on stiffness is substituted into the dynamics model to establish the stiffness evaluation model. Then the mapping relationship between the subsurface crack groups and the dynamic response is obtained. The results show that the different degrees of early subsurface crack failures in different directions have a significant effect on the magnitude of contact stiffness and the area of action. The model not only effectively evaluates the weakening effect on the contact stiffness of ceramic bearings when early subsurface failures occur, but also promotes the stiffness evaluation models of key components using ceramic materials. Graphical abstract: Highlights: Early bearing failures are analyzed as subsurface cracks. Crack quantization reveals the expansion behavior of subsurface cracks. The model reflects the weakening effect of subsurface cracks on contact stiffness. A mapping relationship between dynamic response and failure degrees is obtained.